1992
DOI: 10.1039/dt9920002723
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural, spectroscopic and magnetic studies of two azido and thiocyanato nickel(II) dinuclear complexes with ferromagnetic interactions

Abstract: From a newly synthesised tridentate ligand [pepci = N -(2-pyridin-2-ylethyl)pyridine-2-carbaldimine] two new octahedrally co-ordinated nickel(i1) dimers, [{Ni(pepci) (N3)z}z] 1 and [{Ni(pepci)(NCS),},] 2, have been prepared. The crystal structure 1 has been solved. It crystallizes in space group P2,lc with four formula weights in a cell measuring a = 9.1 98(3), b = 17.382(6), c = 19.356(7) A, and p = 99.57(1)". The structure consists of isolated dimeric units in which the nickel ions are linked by two azide br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 23 publications
7
61
0
Order By: Relevance
“…In fact, as shown in Scheme 1, in complexes with two symmetric end-on azido bridges, the Cu-N azido bond lengths are usually shorter than 2.10 Å and the interaction between the metal ions is often strongly ferromagnetic [4][5][6][7][8][9]. In contrast, complexes bridged by asymmetric end-on azido bridges with both short (£2.10 Å ) and long Cu-N azido bond lengths ( ‡2.20 Å ) are rare, and the interaction between metal centers is weakly ferromagnetic, or even antiferromagnetic [10][11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…In fact, as shown in Scheme 1, in complexes with two symmetric end-on azido bridges, the Cu-N azido bond lengths are usually shorter than 2.10 Å and the interaction between the metal ions is often strongly ferromagnetic [4][5][6][7][8][9]. In contrast, complexes bridged by asymmetric end-on azido bridges with both short (£2.10 Å ) and long Cu-N azido bond lengths ( ‡2.20 Å ) are rare, and the interaction between metal centers is weakly ferromagnetic, or even antiferromagnetic [10][11][12][13].…”
Section: Introductionmentioning
confidence: 93%
“…When the N 3 -anion acts as bridging ligand, normally the end-to-end 1,3-coordination mode gives antiferromagnetic coupling, while the end-on 1,1-mode gives ferromagnetic coupling, but for very large M-μ 1,3 -N 3 -M bond angles the magnetic coupling may be reversed. [16][17][18][19] 2 ] cores have approximately the same angles and distances, and they generally show low ferromagnetic behavior, which was explained by Ginsberg et al [19d] and Duggan et al [19e] Ferromagnetic interactions have been found, generally, in octahedrally coordinated dimeric nickel(ii) complexes with 1,3-thiocyanate [16a,17] and -selenocyanate bridges. [18] When the phenolate acts as a bridging ligand through the oxygen atom in dinuclear nickel(ii) complexes, generally antiferromagnetic behaviour was found; [20][21][22][23] only three complexes showing ferromagnetic coupling have been described in the literature.…”
Section: Introductionmentioning
confidence: 95%
“…The CuÁ Á ÁCu separation in the dimer is 3.304 Å. These values lie in the typical range for double EO azido-bridging copper(II) complexes (2.9004-3.5034 Å) [12,23,[27][28][29][30]. In 1 each dinuclear unit is further linked through single EE azide bridges to four neighboring dimers, leading to a neutral 2D network with a pseudo-honeycomb (6, 3) topology (Fig.…”
mentioning
confidence: 93%